2019
DOI: 10.1152/japplphysiol.00341.2019
|View full text |Cite
|
Sign up to set email alerts
|

Low resting diffusion capacity, dyspnea, and exercise intolerance in chronic obstructive pulmonary disease

Abstract: The mechanisms linking reduced diffusing capacity of the lung for carbon monoxide (DlCO) to dyspnea and exercise intolerance across the chronic obstructive pulmonary disease (COPD) continuum are poorly understood. COPD progression generally involves both DlCO decline and worsening respiratory mechanics, and their relative contribution to dyspnea has not been determined. In a retrospective analysis of 300 COPD patients who completed symptom-limited incremental cardiopulmonary exercise tests, we tested the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 51 publications
2
40
0
2
Order By: Relevance
“…In healthy individuals, the V E /V CO 2 corresponding to the nadir and the V E /V CO 2 at anaerobic threshold are often similar (Figure 2; Sun et al, 2002). The nadir V E /V CO 2 increases progressively with age and is abnormally high in cardiocirculatory and respiratory disease (Sun et al, 2002;Ingle et al, 2012;Elbehairy et al, 2015Elbehairy et al, , 2019Neder et al, 2015;Phillips et al, 2019). Although the nadir V E /V CO 2 is highly reproducible, it may over-estimate ventilatory inefficiency in individuals with poor exercise tolerance and an excessively short test duration during CPET (Neder et al, 2001).…”
Section: E /V Co 2 Nadirmentioning
confidence: 92%
See 1 more Smart Citation
“…In healthy individuals, the V E /V CO 2 corresponding to the nadir and the V E /V CO 2 at anaerobic threshold are often similar (Figure 2; Sun et al, 2002). The nadir V E /V CO 2 increases progressively with age and is abnormally high in cardiocirculatory and respiratory disease (Sun et al, 2002;Ingle et al, 2012;Elbehairy et al, 2015Elbehairy et al, , 2019Neder et al, 2015;Phillips et al, 2019). Although the nadir V E /V CO 2 is highly reproducible, it may over-estimate ventilatory inefficiency in individuals with poor exercise tolerance and an excessively short test duration during CPET (Neder et al, 2001).…”
Section: E /V Co 2 Nadirmentioning
confidence: 92%
“…Airflow limitation, secondary to dynamic respiratory mechanical abnormalities, is generally considered the primary cause of exertional dyspnea in COPD. However, emerging research has suggested that ventilatory inefficiency is also a key contributor to dyspnea and exercise intolerance in patients with COPD (Neder et al, 2015;Elbehairy et al, 2019). In a study examining patients with mild COPD, arterial blood gas-derived dead space and V E /V CO 2 (slope, nadir, and y-intercept) were consistently elevated during exercise while P a CO 2 and alveolar ventilation were similar to age-matched healthy controls (Elbehairy et al, 2015).…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 98%
“…These resting differences are exaggerated throughout exercise, with decreased exercise endurance, increased IND, and increased dyspnea in smokers-at-risk and mild COPD vs. health (108,129). This increased dyspnea has recently been linked to ventilatory inefficiency causing premature mechanical constraint, with individuals with DLCO lower than the lower limit of normal (LLN) experiencing a higher ventilatory requirement and thus greater dyspnea and exercise intolerance than patients with DLCO > LLN despite equivalent spirometry (130). This topic is covered in greater detail in the accompanying review by (104).…”
Section: Using Exercise To Reveal Impairments Hidden At Restmentioning
confidence: 99%
“…We hypothesized that the new approach would prevent bias during ηV ′ E evaluation owing to ventilatory constraints, characteristic of more severe COPD (III/IV), as previously suggested for the V ′ E ‐ V ′CO 2 slope (Neder et al., 2015). Furthermore, as the severity of airflow limitation increases and lung diffusion capacity decreases in the progression from early COPD to more advanced disease (Elbehairy et al, 2019), we should find a linear reduction in ηV ′ E throughout these clinical stages.…”
Section: Introductionmentioning
confidence: 77%